(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
This study was conducted in the light of fiscal plan of Pakistan and secondary data was used from State Bank of Pakistan and Ministry of Finance for year 2000-01 to 2009-10 and linear regression was applied for checking the above said impact, and concludedÂ that the value of R-square which states that all six independent variables of economic development are rightly predicting the development expenditure while using general approach but when we used the stepwise regression method which clearly escaping or leaving three of them and only using remaining three variables namely Health & Nutrition, Exports, and Imports are rightly predicting the development expenditure (Dependent Variable) and states that Health & Nutrition Expenditure is negatively related with development expenditure which is purely policy matter, and Exports, Imports are positively related with development expenditure it is right in the case of exports only but needs serious attention by the policymakers in the case of Imports.